2018
DOI: 10.1007/s40519-018-0518-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of individual circadian rhythm differences on insomnia, impulsivity, and food addiction

Abstract: Level V, descriptive cross-sectional survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 43 publications
3
40
0
2
Order By: Relevance
“…Moreover, a study using a night eating questionnaire to assess night eating syndrome (NES) discovered a moderate negative correlation between chronotype and NES score (r = −0.24, p = 0.015), demonstrating that a higher degree of eveningness causes more prominent NES in the study population [28]. Supplementing this evidence, a recent work also replicated similar finding [49].…”
Section: Eating Behaviormentioning
confidence: 63%
“…Moreover, a study using a night eating questionnaire to assess night eating syndrome (NES) discovered a moderate negative correlation between chronotype and NES score (r = −0.24, p = 0.015), demonstrating that a higher degree of eveningness causes more prominent NES in the study population [28]. Supplementing this evidence, a recent work also replicated similar finding [49].…”
Section: Eating Behaviormentioning
confidence: 63%
“…A number of causal pathways have linked short sleep duration with obesity, as demonstrated by experimental studies [49,50]. For instance, sleep deprivation may stimulate appetite and increase caloric intake [51][52][53] due to a dysregulated production of hormones related to appetite [54,55]. However, findings regarding the association between sleep disturbances and obesity are contradictory, since some studies showed a relationship but others did not confirm the association [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Chronotype is often conceptualized as a psychological construct or a trait [4][5][6]. In this framework, questionnaires assessing diurnal preferences and classifying individuals into types according to a score were developed (e.g.…”
Section: Conceptmentioning
confidence: 99%